Humans and Education in Islam: Optimising Multidimensional Potential for a Cultured and Productive Society - Ika Kartika; Arman Paramansyah; Riyanto; Wiwi Uswatiyah (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
The research aims to analyze humans and education in Islam. The qualitative research method, the type of library research that is explored, is sourced from the library. The author uses a content analysis approach model (research content). This research is an in-depth discussion of the content of written or printed information in the mass media. Data analysis was carried out through content analysis, including all content analysis of the Al-Qur'an text and books related to human themes and education in Islam. The research results show that (1) Humans are multi-dimensional creatures with perception, sensation, and intellectual powers. Human potential is actualized in the form of creative works. (2) Humans are expressed in terms of basyar and insan. Basyar refers to their physical appearance, while insan refers to their psychological qualities, namely the power of feeling and the power of reasoning. (3) Humans and education are two elements that cannot be separated because humans, with all their potential, can be empowered through education and training. Education is an essential part of human life. With education, humans can actualize themselves in the form of work, which is manifested in science, art, and culture. This work is a human effort to overcome the difficulties of life.